A randomized clinical trial comparing safety, clinical and parasitological response to artemether-lumefantrine and chlorproguanil-dapsone in treatment of uncomplicated malaria in pregnancy in Mulago hospital, Uganda - Daniel Kabonge Kaye; Ruth Nshemerirwe; Twaha Serunjogi Mutyaba; Grace Ndeezi (Journal of Infection in Developing Countries)
Background: Malaria infection during pregnancy is a major public health problem. Due to increasing resistance to Chloroquine and Sulphadoxine/Pyrimethamine, the Ugandan national policy on malaria treatment was changed in 2005 to Artemisinin-based combination therapy (ACT) as the first-line treatment for uncomplicated malaria. The policy recommends assessment of safety and efficacy of alternative drugs for treatment of uncomplicated malaria. We compared the efficacy and safety of Artemether-Lumefantrine (Coartem®) and Chlorproguanil-Dapsone (Lapdap®) in the management of uncomplicated malaria in pregnancy. Methodology: We enrolled 110 pregnant women in the second and third trimester of pregnancy who presented to Mulago hospital, Uganda, with uncomplicated malaria. The study design was an open-label randomized clinical trial. Participants were randomized to receive either Artemether-Lumefantrine (Coartem® 20mg/120mg) orally or Chlorproguanil-Dapsone (Lapdap®) orally for 3 consecutive days. Primary endpoints were clinical and parasitological response assessed on days 0, 1, 2, 4, 7, 14 and 28. Adverse effects, clinical response (treatment failure) and parasitological response were compared. Analysis was by intention to treat. Results: Of the 100 women who completed the study, there was no statistically significant difference in clinical and parasitological response by Day 4. The mean fever clearance time 3.0 days with Lapdap® versus 2.5 days with Coartem® was comparable. Likewise, mean parasite clearance time of 2.4 and 2.2 days for Lapdap® and Coartem® respectively was comparable. The adverse effects were comparable between the two groups. Conclusion: Artemether-Lumefantrine and Chlorproguanil-Dapsone have high and comparable cure rates and similar safety profiles when used for treatment of uncomplicated malaria in pregnancy.